School Satisfaction among Adolescents. (2nd January 2017) - Chouhan, Sunita; Bhatnagar, Bharti; Sharma, Madhuri; Kanwar, Ghewar
ABSTRACT: To grow up, the period of transition from childhood to adulthood or dependence on adult direction and protection to self-direction and self-determination is referred as adolescence. Therefore, the present study was undertaken to assess selected areas of School Satisfaction of adolescents studying in private senior secondary schools (co-educational and non-coeducational) of Bikaner city. The total sample for the present study consisted of randomly selected 320 adolescents (13-17 years) of Bikaner city. Data was collected through a standardized tool, that is, the Sharma Adolescent School Satisfaction Inventory. Percentage values were assessing each of the four areas of School Satisfaction. The results revealed that the adolescents had average School Satisfaction. Boys had better School Satisfaction than the girls, whereas, there was no significant difference between School Satisfaction of boys and girls among all the four areas of School Satisfaction. The girls were better than boys in the areas of student themselves and teacher and teaching while for school related curriculum and text books and school plant - organization and administration, the School Satisfaction was better in boys as compared to the girls. School Satisfaction of the girls (coeducational school) was better than the boys and the School Satisfaction of the boys (non co-educational schools) was better than the girls. Thus, it can be concluded that the gender and type of school (co-educational and non co-educational) influence the School Satisfaction of adolescents.